Synthesis of 3-amino-4-hydroxy coumarin and dihydroxy-phenyl coumarins as novel anticoagulants - (:unkn) unknown (GEORG THIEME VERLAG KG, 2010)
Natural and synthetic coumarin derivatives have been shown to possess several beneficial pharmacological effects. The anticoagulation and antithrombotic activities of the 4-hydroxy coumarin derivatives are well known. In this study, besides the 4-hydroxy substituent phenyl and p-methylphenyl derivatives were synthesized and confirmed on the basis of their spectral data. 3-Amino-4-hydroxy coumarin, 5,7-dihydroxy-4-phenyl coumarin and 7,8-dihydroxy-3-(4-methyl-phenyl)coumarin were tested in rats to determine whether they had any effect on vitamin K inhibition by investigating the prothrombin time (PT). PT values of coumarin derivatives were compared with those of warfarin (CAS 81-81-2), which is the most commonly used anticoagulant. 7,8-Dihydroxy-3-(4-methylphenyl) coumarin increased PT when compared to saline treated control group and other coumarins synthesized, 3-amino-4-hydroxy coumarin and 5,7-dihydroxy-4-phenyl coumarin.
Keywords: Anticoagulants; 3-Amino-4-hydroxy coumarin; 7,8-Dihydroxy-3-(4-methyl-phenyl)coumarin; 5,7-Dihydroxy-4-phenyl coumarin; Prothrombin time; Warfarin; ORAL ANTICOAGULANTS; DERIVATIVES; PHARMACOGENETICS